2020
DOI: 10.1186/s42833-020-0009-z
|View full text |Cite
|
Sign up to set email alerts
|

Supercapacitors with alternating current line-filtering performance

Abstract: Alternating current (AC) line filters have been widely used to smooth the leftover AC ripples on direct current voltage. Currently available commercial aluminum electrolytic capacitors (AECs) are primarily used for this application. However, the bulky volume and low capacitance of AECs have become incompatible with the rapidly developed intelligent electronic devices and industry dynamics. Supercapacitors with high specific capacitance and AC line-filtering performance could become the next-generation candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 90 publications
1
28
0
Order By: Relevance
“…Previous work on graphene stacking structures has shown that this system relies on nanosheet slip to detect small mechanical signals. [ 20–23 ] However, direct experimental verification evidence is still lacking. [ 24 ] In particular, it is extremely challenging to directly observe how the relative position of the nanosheet changes the charge transport in the channel.…”
Section: Figurementioning
confidence: 99%
“…Previous work on graphene stacking structures has shown that this system relies on nanosheet slip to detect small mechanical signals. [ 20–23 ] However, direct experimental verification evidence is still lacking. [ 24 ] In particular, it is extremely challenging to directly observe how the relative position of the nanosheet changes the charge transport in the channel.…”
Section: Figurementioning
confidence: 99%
“…Especially, for the past decade, the ultrafast SCs have been investigated to replace the commercial aluminum electrolytic capacitors (AECs) in alternating current (AC) line filtering applications. [16][17][18] AECs are currently used as a reservoir capacitor, smoothing pulsating direct current (DC) signal of 120 Hz (rectified by diodes from a wall AC power outlet of 60 Hz) to a constant DC output voltage required in most line-powered electronics. While the AECs exhibit significantly high-frequency responses greater than ≈10 kHz, their small capacitances with bulky sizes remain one of the main obstacles to scale down circuit boards.…”
mentioning
confidence: 99%
“…[21] The essential requirements of SCs for adequate 60-Hz AC-line filtering applications are fast frequency response characteristics at 120 Hz (e.g., a phase angle close to the ideal capacitor value of −90° and a small resistancecapacitance (RC) time constant less than 8.3 ms at 120 Hz), high areal/volumetric capacitance (responsible for low ripple in the output voltage), and compact size. [17,18,22] Therefore, considerable effort has been devoted to developing high-performance SCs for AC-line filtering applications by investigating key elements such as electrodes, electrolytes, and cell configurations.The electrode is a key component of SCs for closing the power performance gap between the SCs and electrolytic capacitors as well as achieving high capacitance. The traditional SCs based on activated carbon have an extremely slow frequency response, acting as a resistor in the required frequency range for AC line filtering (e.g., phase angle of 0° at 120 Hz).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…54 Also, the use of 2D soft nanomaterials is an emerging technology for the development of micro-supercapacitors with ultra-high volumetric power density. [55][56][57][58] In our case, specific capacitances as high as 277 F g -1 at a current density of 4.5 A g -1 were measured. This last property is based on the pseudocapacitance generated by the oxidation-reduction reactions that can be induced in the 7 conducting dendrimeric film.…”
mentioning
confidence: 99%